The Dielectric and Optoelectronic Properties of Graphene Oxide Films by Solution-Casting Technique - Karteri, Ibrahim; Karatas, Sukru; Cavas, Mehmet; Arif, Bilal; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2016)
Graphene oxide (GO) are successfully prepared onto glass substrates under various conditions in order to obtain graphene oxide films by means of spin coating technique. The GO are prepared by using improved Hummers method as powder. The GO powder is the oxidized form of graphene. The activation energy value of GO powders is determined by using differential scanning calorimetry (DSC). The activation energy for the GO is calculated as 1.62 eV/atom. The structural properties of the GO powder and GO films are characterized with UV-VIS-NIR spectroscopy, FT-IR spectroscopy, scanning electron microscope (SEM) and X-rays diffraction (XRD). The average grain size of the GO are determined as 19.6 nm from Scherrer's equation. The capacitor performance of the Ag/GO/Ag device with AC frequency range from 25 kHz to 100 kHz analyzed. It is investigated that the GO film has very high dielectric constant, accounting for the high capacitance of the device. The electrical and optical parameters such as conductivity, mobility carriers, carrier concentration and band gap (E-g) of the GO films are analyzed. The E-g of the GO films enhanced from 2.1 to 2.8 eV. The band gap values of the films are increased with decreasing different the solution concentration. The (GO) films show that a high transparency. These the findings GO films are crucial for various optoelectronic and photonic devices applications.
Keywords: Graphene Oxide; Optical and Electrical Properties; Activation Energy; Capacitor Performance Solution-Casting